Exploration of the Relationship between Severe and Complex Disabilities and Child Sexual Abuse: A Call for Relevant Research. Issue 7 (3rd October 2019) - Barron, Ian; Allardyce, Stuart; Young, Hannah; Levit, Rebecca
ABSTRACT: Despite the awareness that children with severe and complex difficulties experience child sexual abuse (CSA), the development of research in this area is still in its infancy. This call for relevant research seeks to identify the main gaps in knowledge in order to inform future debate, potential research questions, and raise issues for practice. Themes are identified relevant to researchers and practitioners globally. These include the complexity and duality of definition: recognition of CSA; barriers to communication with children and between services; diversity of segregated and inclusive settings; interaction of age and gender; adult and peer abuse in institutions; sexuality and disability; and intrusive care and medical practices. Recommendations for future research and practice in creating safe environments are provided.